Novel nanoscale signal processing and networking via a wavelength router - Youplao, P.; Mitatha, S.; Yupapin, P. P. (My University, 2010)
This paper presents the very fascinating simulation results of light pulse traveling within a ring resonator system that have shown the unexpected results with various applications. The design system consists of a nonlinear microring/nanoring resonator system incorporating an add/drop filter. The proposed fabricated material used is InGaAsP/InP, which can provide the required output behaviors. Three different forms of input light pulses are Gaussian pulse, dark and bright soliton, whereas the suitable simulation parameters are input power, pulse width, ring radii and the material refractive indices. Three different forms of the results have been interpreted, whereas the dominants behaviors are such as Gaussian soliton, multisoliton and tunable dark soliton, and the potential applications for new laser sources, new communication bands, dynamic optical tweezers and high frequency source THz technology. The use of the proposed system incorporating a nanoscale communication and networking via wavelength router is discussed.